ASPECTOS QUE INFLUENCIAM NA VITALIDADE DAS RUAS COMERCIAIS: UM ESTUDO CROSS-CULTURAL - Barros, Paula (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study is part of a larger research that examines commercial streets as destinations to carry out all sorts of social activities rather than mere paths for walking, cycling, driving, and so forth. To deepen our understanding on the most universal and unique aspects likely to attract and retain people in commercial streets, this research replicates an investigation carried out in the context of United States(Boston metropolitan area, Tampa, Florida and Cincinnati, Ohio). Physical surveys as well as structured and unstructured observations were used to examine stationary social activities on four commercial streets in the touristic centre of Savassi in Belo Horizonte, Brazil. The preliminary findings confirmed that some urban design aspects, land uses as well as personalization, influence the liveliness of commercial streets. However, in Savassi, the evidence indicates that personalization of setbacks with semi-fixed elements to create a sense of 'outdoor room' end to enhance the intensity of street life.